Answer:
x = 45
y = 60
z = 75
Step-by-step explanation:
We can create three different equations with the given variables:
x + y + z = 180
y + z = 3 x
z = y + 15
then we can use this last equation to substitute for 'z" in the second equation:
y + z = 3x
y + y + 15 = 3 x
2 y + 15 = 3 x
x = 2/3 y + 5
Then we can re-write the first equation in terms of y and solve for this unknown:
2/3 y + 5 + y + y + 15 = 180
2/3 y + 2 y = 160
8/3 y = 160
y = 3 * 160 /8
y = 60
Then x = 2/3 (60) + 5 = 45
so x = 45
and finally: z = 60 + 15 = 75
so z = 75